Microangiopatias trombóticas: púrpura trombocitopênica trombótica e síndrome hemolítico-urêmica - Polito, Maria Goretti [UNIFESP] (2010)
Thrombotic microangiopathies (TMAs) are pathological conditions characterized by generalized microvascular occlusion by platelet thrombi, thrombocytopenia, and microangiopathic hemolytic anemia. Two typical phenotypes of TMAs are hemolytic- uremic syndrome (HUS) and thrombotic thrombocytopenic purpura (TTP). Other disorders occasionally present with similar manifestations. Depending on whether renal or brain lesions prevail, two pathologically indistinguishable but somehow clinically different disorders have been described: HUS and TTP. Injury to the endothelial cell is the central and likely inciting factor in the sequence of events leading to TMA. Loss of physiological thromboresistance, leukocyte adhesion to damaged endothelium, complement consumption, abnormal von Willebrand factor release and fragmentation, and increased vascular shear stress may then sustain and amplify the microangiopathic process. Intrinsic abnormalities of the complement system and of the von Willebrand factor pathway may account for a genetic predisposition to the disease that may play a paramount role in particular in familial and recurrent forms. In the case of diarrhea-associated HUS (D+HUS), renal endothelial damage is mediated (at least in large part) by the bacterial agent Shigatoxin (Stx), which is actually a family of toxins elaborated by certain strains of Escherichia coli and Shigella dysenteriae. Outcome is usually good in childhood, Shiga toxin-associated HUS, whereas renal and neurological sequelae are more frequently reported in adult, atypical, and familial forms of HUS and in TTP. Recent studies have demonstrated that deficiency in the von Willebrand factor cleaving protease ADAMTS13, due to deficiency of ADAMTS13 can be genetic or more common, acquired, resulting from autoimmune production of inhibitory anti-ADAMTS13 antibodies, that causes TTP. During the last decade, atypical HUS (aHUS) has been demonstrated to be a disorder of the complement alternative pathway dysregulation, as there is a growing list of mutations and polymorphisms in the genes encoding the complement regulatory proteins that alone or in combination may lead to aHUS. Approximately 60% of aHUS patients have so-called 'loss-of-function' mutations in the genes encoding the complement regulatory proteins, which normally protect host cells from complement activation: complement factor H (CFH), factor I (CFI) and membrane cofactor protein (MCP or CD46), or have 'gain-of-function' mutations in the genes encoding the complement factor B or C3. In addition, approximately 10% of aHUS patients have a functional CFH deficiency due to anti-CFH antibodies. Although TMAs are highly heterogeneous pathological conditions, one-third of TMA patients have severe deficiency of ADAMTS13. Platelet transfusions are contraindicated. Plasma infusion or exchange (PE) is the only treatment of proven efficacy.